An Overview of Energy Sector and Wind Power Potential in Malaysia - S.M, Lawan; W.A.W.Z, Abidin; W.Y, Chai; A., Baharun; T., Masri (SCIENCEDOMAIN international, 2014)
With the new era of industrialization and urbanization, the use of renewable energy is a solution to resolve the impacts of the current dependency on fossil based fuels and hike in fuel prices in the world. The rapid economic development in recent years has led to the energy increase demand in Malaysia and the situation is expected to grow in the near future. The country energy sector is heavily dependent on fossil based fuels for electrical energy generation. Currently, wind energy systems are swiftly gaining recognition as one of the best sources of renewable energy because of its emission free characteristics. This paper reviews the recent scenario and the future expected energy situation in Malaysia. Wind energy resources assessment and potential in Malaysia is also discussed.